Prospective noninterventional study on peripheral blood stem cell mobilization in patients with relapsed lymphomas. Issue 5 (10th September 2016) - van Gorkom, Gwendolyn; Finel, Herve; Giebel, Sebastian; Pohlreich, David; Shimoni, Avichai; Ringhoffer, Mark; Sucak, Gülsan; Schaap, Nicolaas; Dreger, Peter; Sureda, Anna; Schouten, Harry C.
Abstract : High‐dose chemotherapy followed by autologous stem cell transplantation (ASCT) to rescue hematopoiesis is considered standard care for patients with a relapsed chemosensitive lymphoma, but diagnosis of lymphoma has been a risk factor for poor mobilization in several studies. The aim of this prospective noninterventional clinical audit was to review the mobilization strategies used by EBMT centers in relapsed lymphoma and to evaluate their efficacy. Between 2010 and 2014, 275 patients with relapsed lymphoma from 30 EBMT centers were prospectively registered. Almost all patients were mobilized with chemotherapy plus G‐CSF (96%), but there was a large variation in chemotherapy schedules. Thirty (11%) of them were poor mobilizers (<2 × 10 6 CD 34+ cells/kg body weight) at the first mobilization. Poor mobilization was not associated with gender, age, bone marrow involvement at diagnosis, primary diagnosis, number of previous chemotherapy lines, previous radiotherapy or mobilization with G‐CSF alone. The use of high dose cyclophosphamide alone was associated with mobilization failure ( P  = 0.0006), whereas the use of a platinum‐containing regimen was associated with a good mobilization outcome ( P  = 0.013). Because failure rate is low, we can conclude from this study that PBSC mobilization failure in relapsed lymphomas is not an important problem in the EBMT centers.